Epistasis between phenylethanolamine N‐methyltransferase and β2‐adrenergic receptor influences extracellular epinephrine level and associates with the susceptibility to allergic asthma. Issue 3 (15th January 2020) - Sio, Yang Yie; Matta, Sri Anusha; Ng, Yu Ting; Chew, Fook Tim
Abstract: Background: Reduced extracellular epinephrine level often associates with asthma‐related symptoms; however, the correlation between asthma and genetic variants in genes participating in the epinephrine signalling pathway remains unclear. Objective: To characterize the functions of single nucleotide polymorphisms (SNPs) in phenylethanolamine N‐methyltransferase (PNMT) and β2‐adrenergic receptor (ADRB2), and to study the effects, including both direct and epistatic, of these SNPs on serum epinephrine level and asthma susceptibility. Methods: Single nucleotide polymorphisms functions were characterized through in vitro luciferase assay. ADRB2 gene expression level in peripheral blood mononuclear cell (PBMC) was measured by transcriptome sequencing and expression microarray on two separate Asian cohorts (NUS‐UTAR, n = 278 and NUS‐TA, n = 58). Serum epinephrine level was assessed on a Singapore Chinese cohort (NUS‐SH, n = 314) with 155 asthmatic and 159 non‐asthmatic subjects. A separate Singapore Chinese cohort (NUS‐G, n = 3009) was genotyped to show disease association (direct and epistatic effect) of functional SNPs in PNMT and ADRB2. Results: Reduced serum epinephrine level was associated with increased asthma risk in Singapore Chinese. The minor allele of rs876493 was shown to increase PNMT promoter activity and reduce asthma risk. Multiple SNPs in ADRB2 forms a haplotype that was associated with the differential promoter activity of this gene. In this haplotype, rs11168070 was associated directly with ADRB2 expression in PBMCs. Both minor alleles from rs876493 and rs11168070 contribute synergistically to reduce asthma risk and increase serum epinephrine level. Conclusion and Clinical Relevance: Epistatic interaction between genetic variants from PNMT (rs876493) and ADRB2 (rs11168070) is associated with serum epinephrine level and the susceptibility of asthma. Our findings improved the current understanding of the genetic basis of this disease, while genotypic states of these SNPs may serve as potential biomarkers to predict susceptibility to the disease.